Visual and neuropsychological outcomes following paediatric optic pathway glioma - Papini, Chiara (2020)
Survival rates for children with brain cancer have dramatically increased in the recent decades, but evidence demonstrates long-term physical impairments, academic difficulties and neuropsychological deficits even among children with non-aggressive tumours and treatments. Children with optic pathway glioma (OPG) are at risk of neuropsychological difficulties due to the resulting visual impairment, the neural damage of the tumour itself and its treatment, and the comorbid neurodevelopmental disorder called Neurofibromatosis Type 1 (NF1). Yet, the literature on the sequelae of OPG beyond vision is scarce. This thesis is a comprehensive evaluation of long-term visual and neuropsychological outcomes in a group of 12 children who were diagnosed with a glioma in optic pathway, who received either chemotherapy or no treatment for their tumour.